2008
DOI: 10.1111/j.1369-7625.2008.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring informed choice in the context of prenatal testing: findings from a qualitative study

Abstract: Purpose This study explored whether and how a sample of women made informed choices about prenatal testing for foetal anomalies; its aim was to provide insights for future health policy and service provision.Methods We conducted semi-structured interviews with 38 mothers in Ottawa, Ontario, all of whom had been offered prenatal tests in at least one pregnancy. Using the Multi-dimensional Measure of Informed Choice as a general guide to analysis, we explored themes relevant to informed choice, including values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 41 publications
6
41
0
Order By: Relevance
“…11 These principles apply to both invasive and non-invasive tests; however, there is some evidence to show that prenatal testing may be considered by parents as routine rather than optional. 12,13 There are also concerns that prenatal diagnosis itself can be viewed as 'eugenic' and discriminatory against people with disability. 14,15 While service users cite the earlier timing of the test and safety for the fetus 16 as major advantages of NIPD, health professionals were positive, but expressed reservations such as concerns about informed consent and potential 'routinisation' of a test that can be done on a 'simple' blood test.…”
Section: Introductionmentioning
confidence: 99%
“…11 These principles apply to both invasive and non-invasive tests; however, there is some evidence to show that prenatal testing may be considered by parents as routine rather than optional. 12,13 There are also concerns that prenatal diagnosis itself can be viewed as 'eugenic' and discriminatory against people with disability. 14,15 While service users cite the earlier timing of the test and safety for the fetus 16 as major advantages of NIPD, health professionals were positive, but expressed reservations such as concerns about informed consent and potential 'routinisation' of a test that can be done on a 'simple' blood test.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, there is evidence that parents may not be aware that such tests are optional. In a qualitative study of 38 mothers who had undergone prenatal testing, Potter et al 14 found that some women believed they had not given informed consent, mainly because of their beliefs that the testing was a routine part of antenatal care. Authors of the same study found that many women made their decisions based on moral judgements related to their own values, interpreting the factual information provided through their own moral lens.…”
mentioning
confidence: 99%
“…25 Patient autonomy, an underlying principle of informed choice, may be compromised if women feel pressure to accept the screening or if it is not presented as an individual choice. 17,24,26 Pregnant adolescents and younger women may be at particular risk of making non-informed decisions about prenatal screening. They may be more likely to be influenced by health care providers' advice and influence, and are more likely to be socio-economically disadvantaged than adults.…”
Section: What Affects the Ability To Make Informed Decisions?mentioning
confidence: 99%